Adaptasi Sosial Etnis Sunda Di Tengah Masyarakat Jawa: Studi Kasus Desa Palimanan Timur - Bila, Salsa; Nurhilmah, Linda; An Nufus, Fanny; Nasehudin (CV Kalimasada Group, 2025)
This study aims to explore the social adaptation process of Sundanese ethnic individuals living within the predominantly Javanese community of Palimanan Timur Village, Cirebon Regency. Using a descriptive qualitative approach, data were collected through open interviews, participatory observation, and documentation. The findings indicate that Sundanese residents are able to engage actively with the local social environment without abandoning their cultural identity. Adaptation is demonstrated through participation in religious and social activities, the use of Bahasa Indonesia as a means of communication, and openness toward local norms and values. Challenges such as language differences and cultural traits were overcome through consistent interaction and daily immersion. The adaptation process reflects an integrative strategy, in which cultural diversity becomes a foundation for harmonious interethnic relations. These findings reinforce the relevance of social adaptation theory, cultural acculturation, and intergroup contact in shaping social dynamics within multicultural communities.